CREATIVITY AND ADAPTABILITY OF ENTREPRENEURSHIP: THE ROLE OF BRICOLAGE, FASHION BUSINESS MODEL INNOVATION, AND MARKET ORIENTATION IN ENTREPRENEURIAL ENHANCEMENT - Damayanti, Reza (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
In the context of entrepreneurship, bricolage involves the ability to leverage a wide variety of available resources, including knowledge, connections, and capital, to overcome constraints and create added value. The purpose of this study focuses on exploring the mechanisms and effects of how entrepreneurial bricolage affects entrepreneurial performance. The study used a simple randomized method, which was then followed by a face-to-face interview with the company's founder. The results of this study show that the importance of entrepreneurial bricolage and business model innovation in improving entrepreneurial performance, with market orientation moderating the relationship between these variables. It provides valuable insights for business practitioners in devising strategies that suit their market environment. Entrepreneurial bricolage has a significant and positive impact on business model innovation. Business model innovation, in turn, has a significant and positive influence on entrepreneurial performance. It also serves as a complete mediator between entrepreneurial bricolage and entrepreneurial performance. Market orientation plays an important role in regulating the impact of entrepreneurial bricolage on business model